Novel Techniques in Organic Geochemistry applied to Australian Resources - Grotheer, Hendrik (Curtin University, 2017)
The novel analytical techniques hydropyrolysis (HyPy) and compound specific sulfur isotope analysis (CS-S-IA) of organosulfur compounds were tested for their applicability to characterise organic sulfur in geologic formations reflecting sensitive periods of the Earth’s evolution or the deposition of valuable hydrocarbon or mineral resources. Both techniques provide reliable and useful results to be used in mineral exploration (HyPy), as paleoproxy for ancient S-cycle dynamics (CS-S-IA) and understanding kerogen formation processes (HyPy in combination with CS-S-IA).